2010
DOI: 10.1371/journal.pone.0010828
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Methylation Profiles for Multiple Tumor Suppressor Gene Promoters in Salivary Gland Tumors

Abstract: BackgroundMethylation profiling of tumor suppressor gene (TSGs) promoters is quickly becoming a powerful diagnostic tool for the early detection, prognosis, and even prediction of clinical response to treatment. Few studies address this in salivary gland tumors (SGTs); hence the promoter methylation profile of various TSGs was quantitatively assessed in primary SGT tissue to determine if tumor-specific alterations could be detected.MethodologyDNA isolated from 78 tumor and 17 normal parotid gland specimens was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 41 publications
(54 reference statements)
1
35
1
1
Order By: Relevance
“…14 Each reaction was carried out in a reaction volume of 10 μL, with components as previously described. 4 Calibration curves were constructed for each plate with serial dilutions of bisulfite-converted universal methylated human DNA (Zymo Research, Irvine, California). Each plate included samples, water blanks, and calibration curves in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…14 Each reaction was carried out in a reaction volume of 10 μL, with components as previously described. 4 Calibration curves were constructed for each plate with serial dilutions of bisulfite-converted universal methylated human DNA (Zymo Research, Irvine, California). Each plate included samples, water blanks, and calibration curves in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly a promoter methylation study performed on several TSG’s including FHIT showed that FHIT promoter methylation rates were actually much higher in normal tissue than in benign or malignant salivary gland tumors (100) . The reason for this inverse relationship is unclear.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
“…Published reports on methylation in ACC mostly focus on candidate genes known to play important roles in non-ACC tumors (100, 118123) . In some studies, differentially methylated genes were further correlated with available clinical and pathological parameters of the given tumor samples (121, 122) , to identify their biological function and clinical importance ( see Table 3).…”
Section: Dna Methylation In Accmentioning
confidence: 99%
“…UVI5008 treatment of HCT116-DKO did not further enhance transcription as compared with the parental HCT116 suggesting that its DNMT but not HDAC and/or SIRTi caused the low but significant activation of the UCHL1 locus in wild-type cells. TIMP3, a TSG known both to be repressed by DNMT (39,40) and to be SIRT1 target (41) was reactivated by UVI5008 only in HCT116-DKO cells and not in the untreated or wild-type cells (Fig. 5C).…”
Section: Uvi5008 Reactivates Tsg Programsmentioning
confidence: 99%